Endoscopic tumor diagnosis and treatment - Gaddam, Srinivas; Edmundowicz, Steven A. (Endoscopy, 2013)
This year’s Digestive Disease Week (May 18 – 21, 2013, Orlando, Fla) presented new perspectives on endoscopic diagnosis and management of GI tumors. These abstracts can be broadly divided into tumors of the upper and lower GI tract and pancreatobiliary tumors.